A Tracer Study on the Graduates of Master of Arts: A Case Study at a Polytechnic College in La Union, Philippines - Florendo Jr, Artemio L.; Regacho, Rosebelita Ting (Jurnal Pendidikan Indonesia Gemilang, 2024)
Graduate education is crucial for national progress and modernization, as it trains, educates, and develops a workforce capable of empowering human life and responding to changing societal needs. The study examined students' expectations of employment opportunities, focusing on high demand and expected growth rates. A descriptive research design was utilized using a survey questionnaire to gather the needed data. The study was conducted at a Polytechnic College in La Union, Philippines during the first semester of the 2019 – 2020 academic year, with a total sample size of 73. The study revealed that the M.A. graduates were mostly married females aged 36-40 handling Teacher II positions. However, challenges like time constraints, distance, and excessive paperwork necessitate program improvements. A Polytechnic College in La Union, Philippines should regularly follow up with M.A. graduates, enhance faculty training, provide scholarship grants, offer affordable options, update graduate programs, and improve physical facilities and resources.